Proposal of solutions to promote investments for R&D in Vietnam – vision from international experiences - Tuan, Nguyen Quang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
Investment for R&D is one of the highly important indexes for analysis and assessment of the national innovation system. Given the index of the total social investment (percentage of GDP) we can have certain ideas on the level of development of the economy in general and of the national innovation system in particular. From the point of view of the national innovation system through presentations of some related workshops, this paper makes focus on analysis of investment for R&D from some countries and companies in the world and then proposes directions of solution for increasing social investment for R&D in Vietnam. Code: 19092401